Hard Truths about Heart Work: An interview with Jennie Chua - Lien Centre for Social Innovation (Institutional Knowledge at Singapore Management University, 2011)
Just as there are calls for leadership to bridge the business and social worlds, there are also calls for new models and inspiration in the nonprofit sector. Social Space catches up with the inimitable Jennie Chua,fundraiser and chairman of the Community Chest, to hear her thoughts on these issues. True to form, Jennie delivers a few hard truths about fundraising and charity in Singapore.